Pengaruh Independensi, Akuntabilitas, Time pressure dan Due Professional Care Terhadap Kualitas Audit pada Inspektorat Musi Banyuasin Sekayu - Fitri Rahayu, Pipit; Armereo, Crystha (Akuntansi dan Manajemen, 2019)
The purpose of this study are to determine the independence, accountability, time pressure and due professional care on the audit quality of the Inspektorat Musi Banyuasin in Sekayu. While the population used in this study were all auditors in the Inspectorate of Musi Banyuasin Sekayu to 67 people. The sample that used is 67 people using a census is all the populations sampled. Technique to analyze data are multiple regression analysis with SPSS 20 software tools. The results of the study partially indicate that: (1) independence has a negative effect and not significant towords the audit qualitry of Inspectorate of Musi Banyuasin Sekayu, (2) accountability has a positive effect and not significant towords the audit qualitry of Inspectorate of Musi Banyuasin Sekayu, (3) time pressure has a positive effect and significant towords the audit qualitry of Inspectorate of Musi Banyuasin Sekayu, and (4) due professional care has a positive effect and not significant towords the audit qualitry of Inspectorate of Musi Banyuasin Sekayu. And the results of the simultaneous testing also show that independence, accountability, time pressure and due professional care have a positive and significant effect on the audit quality of Inspectorate Musi Banyuasin Sekayu.